Design and reanalysis of pile cap with five piles under eccentricity - Maged Abdullah Abdulhak Al-Esaei, 1993- (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia